EVALUASI PELAKSANAAN PROGRAM PENGENALAN LAPANGAN PERSEKOLAHAN (PLP) TERHADAP KESIAPAN CALON GURU VOKASI PENDIDIKAN TEKNIK BANGUNAN ANGKATAN 2021 - Hutauruk, Stevi; Liana Atika; Harun Sitompul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to evaluate the implementation of the School Field Introduction Program (PLP II) on the readiness of vocational teacher candidates in Building Engineering Education, class of 2021, Universitas Negeri Medan. The evaluation model applied is CIPP (Context, Input, Process, Product). A quantitative approach was employed using questionnaires covering aspects of administration, coordination, communication, student involvement, and the effectiveness of supervision by lecturers and mentor teachers. The findings indicate that PLP II contributes positively to students’ readiness as vocational teachers, although challenges remain in administration, coordination, and teaching creativity. This evaluation is expected to provide recommendations for improving the quality of PLP implementation in the future.